A Model Driven Approach based on Interaction Flow Modeling Language to Generate Rich Internet Applications - Sarra Roubi; Mohammed Erramdani; Samir Mbarki (International Journal of Electrical and Computer Engineering (IJECE), 2016)
A Rich Internet Applications (RIAs) combine the simplicity of the hypertext paradigm with the flexibility of desktop interfaces. These appliations were proposed as a solution to follow the rapid growth and evolution of the Graphical User Interfaces. However, RIAs are complex applications and their development requires designing and implementation which are time-consuming and the available tools are specialized in manual design. In this paper, we present a model driven approach to generat GUI for Rich Internet Application. The approach exploits the new language IFML recently adopted by the Object Management Group. We used frameworks and technologies known to Model-Driven Engineering, such as Eclipse Modeling Framework (EMF) for Meta-modeling, Query View Transformation (QVT) for model transformations and Acceleo for code generation. The approach allows to quickly and efficiently generating a RIA focusing on the graphical aspect of the application.